2023
DOI: 10.1136/bmjopen-2022-070054
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the views of low-acuity emergency department consulters on an educational intervention and general practitioner appointment service: a qualitative study in Berlin, Germany

Abstract: ObjectivesLow-acuity patients presenting to emergency departments (EDs) frequently have unmet ambulatory care needs. This qualitative study explores the patients’ views of an intervention aimed at education about care options and promoting primary care (PC) attachment.DesignQualitative telephone interviews were conducted with a subsample of participants of an interventional pilot study, based on a semi-structured interview guide. The data were analysed through qualitative content analysis.SettingThe study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The authors suggested that there should be services to enable patients to find a GP who meets their individual needs, arguing that this would increase GP attachment and continuity of care in the long term [ 34 ]. A targeted GP attachment program, as piloted in the interventional module of EMAPREPARE, could help to connect patients with GPs [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors suggested that there should be services to enable patients to find a GP who meets their individual needs, arguing that this would increase GP attachment and continuity of care in the long term [ 34 ]. A targeted GP attachment program, as piloted in the interventional module of EMAPREPARE, could help to connect patients with GPs [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be very helpful in targeting future intervention approaches to promote PC attachment and continuity of care and in turn strengthen GP-mediated health literacy. Our EMAPREPARE pilot intervention is a first step in this direction, providing both information material about alternative care paths and an optional GP appointment scheduling service [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations